(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
The study aims at examining the urgent changes in the Israeli position from the Syrian crisis (2011-2017) which came as a result of the complexities of the positions of the conflicting parties to the conflict and the problems it left for Israel in visualizing the final status in line with its strategic interests. This made Israel deal with the crisis from the beginning in a tactical manner, and according to the updates imposed. Thus, the Israeli position on the crisis has undergone several transformations, influenced to a large extent by the development of its events, which is linked to the set of international and regional changes intertwined with it. This position ranged between the state of ambiguity, and sometimes limited intervention during the first years of the crisis, and the sufficiency of relying on the United States to protect its interests, and direct military action after the Russian intervention in 2015, to confront the threats to its national security, represented mainly by the growing of the Iranian controlling power from its northern border.